2019
DOI: 10.4186/ej.2019.23.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Bimodal Mesoporous Silica Derived from Rice Husk Ash

Abstract: This study was able to obtain bimodal mesoporous silica through a process of synthesizing silica derived from rice husk ash in conjunction with structure-directing agents (Pluronic P123 and cetyltrimethyl ammonium bromide (CTAB)) and the application of the sol-gel method. Rice husk ash taken from a biomass power plant went through a process of extraction using sodium hydroxide. The procedures of X-ray diffraction, X-ray fluorescence spectrometer, Fourier-transform infrared spectrometer, N2 adsorption-desorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…In general, commercial materials such as tetraethyl orthosilicate (TEOS) [23][24][25] and sodium silicate [26][27] are utilized as silica precursors in the production of SBA-15, which are, of course, relatively expensive. Several natural materials have been used as a source of silica in the synthesis of SBA-15, including sugarcane bagasse [28], brickyard ash [29], coal gangue [30], oil palm ash [31], and rice husk ash [32][33][34], to reduce production costs. Rice husk ash is the most potent natural material because it contains more than 90% of SiO 2 [35][36][37].…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, commercial materials such as tetraethyl orthosilicate (TEOS) [23][24][25] and sodium silicate [26][27] are utilized as silica precursors in the production of SBA-15, which are, of course, relatively expensive. Several natural materials have been used as a source of silica in the synthesis of SBA-15, including sugarcane bagasse [28], brickyard ash [29], coal gangue [30], oil palm ash [31], and rice husk ash [32][33][34], to reduce production costs. Rice husk ash is the most potent natural material because it contains more than 90% of SiO 2 [35][36][37].…”
Section: ■ Introductionmentioning
confidence: 99%
“…SBA-15 is typically synthesized using the hydrothermal technique [23][24][25][26][27][28][29][30][31][32][33][34], which involves heating the reactants with air in a closed container (autoclave). The hydrothermal approach is less cost-effective and does not adhere to the green chemistry principle since it takes a long time and a lot of energy to complete the reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous research has revealed that mesopore silica can function as a catalyst [2], drug delivery [3,4], and adsorbent [5]. This is because mesoporous silica has a large specific surface area with regular pores.…”
Section: Introductionmentioning
confidence: 99%
“…This process will cause each hole to collide with each other, which affect to create a window within the material. Eventually, the gel is continually dried at 100 ºC to make the structure more organized, and followed by template removal process with calcination under air atmosphere or solvent extraction using ethanol in order to dispose the contaminant such as unreacted substrate [43,44] as figure 2.2. -C) Mesoporous carbon has been fascinated significant attendance because of their use as catalyst support for many reactions, which is a large pore volume, surface area, and pore size [45].…”
Section: Properties Of Mesoporous Silicamentioning
confidence: 99%
“…In addition, Barrett-Joyner-Halenda (BJH) method based on the Kelvin equation was also applied to determine the pore structure of samples [44].…”
Section: Characterization Of Mesocellular Foam Materials Nitrogen-phy...mentioning
confidence: 99%